2017
DOI: 10.1097/qai.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facility- and Community-Based Peer Support Models on Maternal Uptake and Retention in Malawi's Option B+ HIV Prevention of Mother-to-Child Transmission Program: A 3-Arm Cluster Randomized Controlled Trial (PURE Malawi)

Abstract: Facility- and community-based peer support interventions can benefit maternal uptake and retention in Option B+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 16 publications
4
99
1
Order By: Relevance
“…6 The positive effect of peer support was primarily seen in the period between 12 and 24 months after ART initiation. Rates of attrition were between 30% and 40% less among women receiving expert peer support.…”
Section: Peer Support Interventions and Retention In Care And Other Hmentioning
confidence: 99%
“…6 The positive effect of peer support was primarily seen in the period between 12 and 24 months after ART initiation. Rates of attrition were between 30% and 40% less among women receiving expert peer support.…”
Section: Peer Support Interventions and Retention In Care And Other Hmentioning
confidence: 99%
“…Third, facility--and community--based interventions are needed to increase rates of retention--in--care of mothers, regardless of feeding practice. In Malawi, effective peer support increased postnatal retention in care and associated ART adherence to over 80% at 24 months with improved viral suppression and reduced resistance110 .…”
mentioning
confidence: 99%
“…Follow-up of participants was completed on July 31st, 2016. The final results and outcomes (per protocol) of this study are reported elsewhere [13]. Alongside this trial, a qualitative study has been implemented to explore experiences of patients and health care workers in relation to the implementation of Option B+ and the trial interventions [14].…”
Section: Discussionmentioning
confidence: 99%